Association of Tibetan Habitual Food and Metabolic Syndrome Among Tibetan People in China: A Cross-Sectional Study - Li, Kehan; Zhang, Qiang; Cai, Hui; He, Ruifeng; Nima, Qucuo; Li, Yajie; Suolang, Deji; Cidan, Zhuoga; Wangqing, Pingcuo; Zhao, Xing; Li, Jingzhong; Liu, Qiaolan (Frontiers in Nutrition, 2022)
Background Association between habitual food intake in Tibet and metabolic syndrome (MetS) is largely unclear. Objective To examine the association between Tibetan habitual food intake and MetS among Tibetan adults. Methods A population-based cross-sectional study, the China Multi-Ethnic Cohort (CMEC) study, was conducted between 2018 and 2019. We used data of all Tibetans in the CMEC in the current study. Participants, 1,954 males and 3,060 females and aged 18-79 years, were from Lhasa, Tibet Autonomous Region. Habitual dietary intake was assessed using a food frequency questionnaire. MetS was defined according to ATP III guidelines. Multivariate logistic regression was used to estimate the association between five Tibetan habitual foods and MetS. Results Tsampa, butter tea, and Qing cha intake were associated with reduced prevalence of MetS. Compared with the lowest quartile of each food, odds ratios and their 95% confidence intervals (95% CIs) of medium and high tsampa intake were 0.59 (0.41-0.85) and 0.53 (0.36-0.77), ORs (95% CIs) of butter tea were 0.67 (0.52-0.88) and 0.61 (0.46-0.81), and Qing cha were 0.85 (0.71-1.03) and 0.75 (0.60-0.93), respectively. When exploring the joint effects of these three foods on MetS, the adjusted ORs and their 95% CIs were 0.65 (0.49-0.87) for the middle intake group and 0.59 (0.42-0.83) for the high intake group as compared with the never/rarely group (P = 0.022 for trend). Associations of MetS with Tibetan noodles and raw beef were not observed. Conclusion Tsampa, butter tea, and Qing cha were negatively associated with MetS. Recommendation of increasing intake of these foods may be beneficial to MetS prevention.